EVALUATION OF GaP SINGLE CRYSTALLINE MATRIX SUBSTRATES THICKNESS PREPARED BY SEPARATED GROWTH METHOD IN THE SYSTEM Sn- Ga / InP - Arkhipov, Yu. V.; Askaruly, A.; Bychenkov, V. Yu.; Tkachenko, I. M. (Recent Contributions to Physics, 2008)
The thickness estimation method of GaP single crystalline matrix substrates prepared by separated growth method is suggested. Possibility of less than 20nm matrix substrates formation is shown.